Mathematische Modelle in der Biologie: 4.6. bis 10.6.1978 - Hadeler, Karl-Peter; Jäger, Willi; Levin, Simon Asher (Tagungsbericht, 1978)
W. Alt, Heidelberg; D. G. Aronson, Minneapolis; G. Becker, Göttingen;H. J. Bremermann, Berkeley; J. M. Cushing, Tucson; O. Diekmann, Amsterdam; K. Dietz, Tübingen; Th. Eisele, Heidelberg; G. Gerisch, Basel; U. von Hehn, Tübingen; U. an der Heiden, Tübingen; R. Heinrich, Berlin DDR - verhindert; I. Heuch, z. Zt. Tübingen; P. Holgate, London; D. Mandallaz, Basel; H. Maurer, Münster; H. Meinhardt, Tübingen; J. A. J. Metz, Leiden; M. Mimura, Kobe; H. G. Othmer, New Brunswick; L. A. Peletier, Leiden; T. Poggio, Tübingen; E. T. Poulsen, Aarhus; A. Reissland, Bielefeld; J. Rinzel, Bethesda; O. E. Rössler, Tübingen; F. Rothe, Tübingen; L. A. Segel, Rehovot; R. Sperb, Basel; P. Tautu, Heidelberg; A. Tesei, Rom; H. Thieme, Münster; A. Wörz-Busekros, Tübingen
Keywords: Konferenzschrift